PERTUMBUHAN DAN DAYA HASIL TUMPANG SARI JAGUNG (Zea mays L.) DAN KACANG TANAH (Arachis hypogaea L.) TERHADAP WAKTU DAN POSISI PEMANGKASAN JAGUNG - Ema Susanti; Susylowati Susylowati; Hadi Pranoto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
The purpose of the research was to know the effect of time and topping position of corn and the interaction between the factor on the growth and yield capacity of intercropping corn and peanuts. This study was conducted since April to August, 2016 at experiment farm land Faculty of Agriculture Mulawarman University, in Teluk Dalam village, Subdistrict Tenggarong Kutai Kartanegara. Factorial experiment 3x3 was arranged in Randomized Complete Block Design (RCBD) with three replications. The first factor was topping time of corn (W), in three levels, namely 45 days after planting (DAP) (w1), 55 days after planting (DAP) (w2), and 65 days after planting (w3). The second factor was the position of topping corn (P), in three levels, namely topping all leaves below the cobs (p1), topping of stalks above cobs (p2), and topping of tassel (p3). The results oe the research showed that topping time of corn was significantly different on dry seeds of corn per plot and dry seeds of corn per hectare, but it was not significantly different on other variables. Treatment topping time 65 DAP (w3) resulted the highest dry seeds of corn per hectare, that is 2.67 Mg ha-1 and dry seeds of peanuts per hectare, that is 0.59 Mg ha -1. The treatment of topping position was significantly different on the length of cob without husks, cob diameter, number of seeds per cobs, dry seeds of corn per plot and per hectare, however it was not significantly different on other variables. The highest dry seeds of corn per hectare obtained by treatment topping of tassel (p3) that is 2.88 Mg ha-1 and the highest of results peanut seeds per hectare obtained by treatment topping all leaves below the cobs (p1) that is 0.60 Mg ha-1. The interaction between time and topping position of corn was significantly different on diameter of cob, dry seeds of corn per plot and per hectare, but it was not significantly different on other variables. The highest dry seeds of corn per hectare obtained at interaction of topping time 45 days after planting (DAP) and the topping of tassel (w1p3) i.e. 3.19 Mg ha-1  while the highest of dry seeds of peanuts per hectare obtained at interaction of topping time 45 DAP and topping position all leaves below the cobs (w1p1) i.e. 0.61 Mg ha-1. The treatment of topping of tassel (p3) resulted the highest value of Land Equivalent Ratio (LER) is 1.65.